1990
DOI: 10.1002/elps.1150110402
|View full text |Cite
|
Sign up to set email alerts
|

Steady state electrolysis and isoelectric focusing

Abstract: The properties of pH gradients formed by stationary electrolysis of weak mobile or fixed electrolytes are analyzed. The model uses the appropriate balance equations and those of chemical equilibria. It is shown how the equation of the current density has to be modified for considering that fraction of current that is associated with the diffusion of neutral buffer molecules within a pH gradient. Furthermore it is shown that the pH gradients themselves give rise to water production within the gradient and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Electrodes placed either in or directly adjacent to the Histology showed that in 17 rats 'electrolytic segmentectomy' resulted in destruction of the entire tumour de-tumours cause tumour cell death by the localised production and action of cytotoxic electrode products [34,35]. posit (7/11 left lobe and 10/11 right lobe).…”
Section: Resultsmentioning
confidence: 99%
“…Electrodes placed either in or directly adjacent to the Histology showed that in 17 rats 'electrolytic segmentectomy' resulted in destruction of the entire tumour de-tumours cause tumour cell death by the localised production and action of cytotoxic electrode products [34,35]. posit (7/11 left lobe and 10/11 right lobe).…”
Section: Resultsmentioning
confidence: 99%
“…(3) with a term accounting for chemical conservations-provided the above definition of a i is used. This definition automatically ensures the conservation of the total concentration of a buffer constituent [17].…”
Section: Theorymentioning
confidence: 99%
“…(2) the total concentration of a species is related to its charged fractions. It is possible to express a i as a function of pH only [16,17].…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Electrolytic abla tion, also known as lowlevel direct current therapy, is an al ternative method which produces no change in temperature and exerts its effects through electrochemical and pH modi fications and the production of free radicals. These changes render the microenvironment close to the probe extremely cytotoxic, produce tissue necrosis and are not influenced to any large degree by the presence of blood vessels or bile ducts [39,40] . Due to the almost complete absence of thermal energy developed, the procedure has proved particularly safe in experimental studies where ablations were conduct ed close or even within major vessels (Figure 1) [4143] .…”
Section: Proximity To Large Vesselsmentioning
confidence: 99%